Aprendizagem de idiomas modernos: percepções de estudantes universitários de graduação - Lozada Trimbath, Minnie (2000)
Teachers know that when programming the studies to be carried out in an educational institution, it is necessary to start from a diagnosis, which must be updated periodically. Although this includes a series of variables, the emphasis in the investigation of these variables may vary. In this case, and thinking that we lack greater knowledge about one of them, a study has been carried out at the Universidad Nacional Mayor de San Marcos in order to better understand the way undergraduate university students think about learning modern languages other than Spanish.